(untitled) (XXI Century. Spanish Literature and Culture, 2020)
Luis Antonio de Villena offers us a reading of a Juan Gil-Albert, who was an aesthete and a symbolist in his early literary works. A child of the bygone age of decadent symbolism, the influence of such writers as Oscar Wilde, Miró and the early Valle Inclán, persists in early writings like La fascinación de lo irreal (1927) and Vibración de estío (1928). The literary strangeness of this initial Gil-Albert stems from the fact that he was caught “between” an obsolete aesthetic and an age of “literary diversity”: an aesthetic of decadent features adopted at the height of of modernity.